HOW PRO-INFLAMMATORY WESTERN DIETS AND ANTI-INFLAMMATORY DIETARY INTERVENTIONS INFLUENCE NONALCOHOLIC FATTY LIVER DISEASE (NAFLD) PROGRESSION: A NARRATIVE REVIEW OF NUTRITIONAL MECHANISMS OF ACTION - Wedharga, I Gede Putu Adhi (JURNAL WIDYA MEDIKA, 2025)
Unhealthy diets, such as Western-type diets, are major contributors to metainflammation underlying the progression of nonalcoholic fatty liver disease (NAFLD). This narrative review analyzed 10 studies (2014–2024) from Google Scholar and PubMed to explore dietary roles in NAFLD progression. Western-type, hypercaloric, high-fructose, and HFHS diets worsen NAFLD by increasing inflammatory biomarkers and reducing oxidative stress. Conversely, dietary interventions, including the DASH diet, freshwater fish–based diets, and the Mediterranean diet, attenuate metainflammation and slow NAFLD progression. The significance of this topic lies in the global health burden of NAFLD and the increasing recognition of metainflammation as a key driver of its progression. While several pharmacological candidates have shown promise, dietary strategies remain essential in clinical practice due to their accessibility, safety, and preventive potential. This review underscores the clinical relevance of targeting metainflammation through specific dietary interventions and offers insights for both therapeutic guidance and public health policy.